Differentiation-dependent Requirement of Tsix long non-coding RNA in Imprinted X-chromosome Inactivation - Maclary, Emily (2014)
Imprinted X-inactivation is a paradigm of mammalian transgenerational epigenetic regulation resulting in silencing of genes on the paternally-inherited X-chromosome. The pre-programmed fate of the X-chromosomes is thought to be controlled in cis by the parent-of-origin-specific expression of two long non-coding RNAs, Tsix and Xist, in mice. Exclusive expression of Tsix from the maternal–X has implicated it as the instrument through which the maternal germline prevents inactivation of the maternal–X in the offspring. Here, we show that Tsix is dispensable for inhibiting Xist and X-inactivation in the early embryo and in cultured stem cells of extra-embryonic lineages. Tsix is instead required to prevent Xist expression as trophectodermal progenitor cells differentiate. Despite induction of wild-type Xist RNA and accumulation of histone H3-K27me3, many Tsix-mutant X-chromosomes fail to undergo ectopic X-inactivation. We propose a novel model of lncRNA function in imprinted X-inactivation that may also apply to other genomically imprinted loci.